The skin prick test – European standards. Issue 1 (1st February 2013) - Heinzerling, Lucie; Mari, Adriano; Bergmann, Karl‐Christian; Bresciani, Megon; Burbach, Guido; Darsow, Ulf; Durham, Stephen; Fokkens, Wytske; Gjomarkaj, Mark; Haahtela, Tari; Bom, Ana Todo; Wöhrl, Stefan; et al.
Abstract: Skin prick testing is an essential test procedure to confirm sensitization in IgE‐mediated allergic disease in subjects with rhinoconjunctivitis, asthma, urticaria, anapylaxis, atopic eczema and food and drug allergy. This manuscript reviews the available evidence including Medline and Embase searches, abstracts of international allergy meetings and position papers from the world allergy literature. The recommended method of prick testing includes the appropriate use of specific allergen extracts, positive and negative controls, interpretation of the tests after 15 – 20 minutes of application, with a positive result defined as a wheal ≥3 mm diameter. A standard prick test panel for Europe for inhalants is proposed and includes hazel ( Corylus avellana ), alder ( Alnus incana ), birch ( Betula alba ), plane ( Platanus vulgaris ), cypress ( Cupressus sempervirens ), grass mix ( Poa pratensis, Dactilis glomerata, Lolium perenne, Phleum pratense, Festuca pratensis, Helictotrichon pretense ), Olive ( Olea europaea ), mugwort ( Artemisia vulgaris ), ragweed ( Ambrosia artemisiifolia ), Alternaria alternata ( tenuis ), Cladosporium herbarum, Aspergillus fumigatus, Parietaria, cat, dog, Dermatophagoides pteronyssinus, Dermatophagoides farinae, and cockroach ( Blatella germanica ). Standardization of the skin test procedures and standard panels for different geographic locations are encouraged worldwide to permit better comparisons for diagnostic, clinical and research purposes.